Small Business, Big Society - Hodder, Rupert (Springer Singapore, 2018)
This book considers how small businesses stir up changes in social relationships and what these changes mean for wider society. From this emerges a challenging and provocative discussion on the problems facing both the developing and developed worlds. Development, it argues, is written into social relationships and growth follows attempts to avoid the market's degenerative effects. What this discussion means for development practice, and for thought in the social sciences more generally, is also considered. If there is a watchword for development practice, then it is acceptance - acceptance of more social, less prescriptive, and far more experimental modes of working. As for the implications of these ideas for social science, these may be described well enough as an economy of ontology.